KEARIFAN LOKAL YANG TERCERMIN DALAM CERITA RAKYAT MASYARAKAT MELAYU KAPUAS HULU - Syamsiah, Syamsiah; Martono, Martono; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was motivated by researchersâ€™ concerns about oral literature that were almost extinct and forgotten by the community. The problem of this research was devoted to local wisdom which was reflected in the folklore of the Kapuas Hulu Malay community which was divided into four problems,Â namely how local wisdom relates to belief systems, livelihood system, local norm, and the implementation of literary learning in schools. Based on these problems, the purpose of this study was to describe the belief system, livelihood system, and local norm reflected in the folklore of the Kapuas Hulu Malay community, as well as the implementation of learning in schools. There are eight foklore to be analyzed, namely Gumak dengan Adekia, Apang Aloi Beuma, Batu Lobor, Bunga Simpor, Apang Sekumang dan Apang Saji, Kenturon Antu Remaong, and Tok Paga dan Si Katamba.The result of this study was first: the belief system is divided into two, namely believing in superanatural things and believing in ghosts. Second: the livelihood system is divided into four namely farming (farmers), fishermen, hunting and gathring, and trading. third: local norm were divided into three, namely, local norm related to oneself, local norm that relate to humans and other human beings, and local norm that relate to humans and God. Keywords: Local wisdom, foklore